Crowdfunding- An International Comparison and Analysis of the Constraints and Opportunities for Implementing it in Portugal - Terjung, Johanna Elisabeth (2018)
Crowdfunding evolved as part of the world’s progress towards a global and digital society. Over the past years, leveraging the ‘power of the crowd’ has become an increasingly popular way to obtain financing. This research is an effort to analyse the extend to which Crowdfunding is used as a form and source of financing for start-ups in Portugal. As such, this dissertation is an empirical work encompassing an extensive literature review on the concept of Crowdfunding, its origin, development and current state and offers an analysis for the case of Portugal. Through elite interviews with operators of existing platforms in Portugal, Portuguese start-ups and finance experts familiar with the market, the research question receives a thorough examination concluding that Crowdfunding has the potential to become a viable form of financing for start-ups in Portugal.